Conjugated Hyperbilirubinemia in Infants: Is There Still a Role for ERCP? - Jan Stovicek; Stepan Hlava; Radan Keil; Jiri Drabek; Jindra Lochmannova; Petra Koptová; Martin Wasserbauer; Barbora Frybova; Jiri Snajdauf; Radana Kotalova; Michal Rygl (Canadian Journal of Gastroenterology and Hepatology)
Over a twenty-year period, we performed 255 ERCP procedures in infants aged up to 1 year. ERCP was indicated in cholestatic infants with suspicion of biliary obstruction. The most common diagnosis was biliary atresia (48%), choledochal cysts (13%), and choledocholithiasis (4%). The procedure complication rate was 13.7%. Hyperamylasemia occurred in 12.9%. More severe complications were rare‐0.8% of ERCP procedure. There were no cases of postprocedural pancreatitis or death. Our study has proved that ERCP is a safe and reliable method in this age group. Its high specificity and negative predictive value for extrahepatic biliary atresia can prevent unnecessary surgeries in patients with normal bile ducts or endoscopically treatable pathologies.